Anthroposophieforschung Forschungsstand - Perspektiven - Leerstellen - Vitanova-Kerber, Viktoria; Zander, Helmut (Okkulte Moderne, 2023)
Rudolf Steiner's (1861-1925) anthroposophy is present in society (Waldorf schools, Weleda, Demeter...) but not in scholarly research. This volume is the first to present academic research articles that close this gap by delving into examples, documenting the state of research for selected topics, and helping to establish anthroposophy studies in the academic field.